2006
DOI: 10.1007/s00299-006-0232-4
|View full text |Cite
|
Sign up to set email alerts
|

Induction and cryopreservation of embryogenic cultures from nucelli and immature cotyledon cuts of mango (Mangifera indica L. var Zihua)

Abstract: In this paper, we described the direct somatic embryogenesis from both immature cotyledon cuts and nucelli in the same mango cultivar (Mangifera indica L. var Zihua), studied the effect of growth conditions of embryogenic cultures (EMs) on cryopreservation and compared the cryopreservation response of EMs induced from these two different explants. Histological studies demonstrated that EMs derived from nucelli could be induced directly from epidermal cells of both sides of nucelli, whereas EMs derived from cot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…However, we achieved the successful cryopreservation of P. omorika ET without prior coldhardening, and this reduced the costs and duration of preculture. A few reports on the effect of cryopreservation of the ET of coniferous tree species on their later potential for embryogenesis have shown that the proliferation potential of ET is the same as that of non-frozen control tissues (Kartha et al 1988;Lardet et al 2007;Wu et al 2007). However, we observed some differences in the growth rate of fresh ET on day 28 of culture, which amounted to 19.18 ± 2.0 and 16.00 ± 1.5 g in two control variants (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…However, we achieved the successful cryopreservation of P. omorika ET without prior coldhardening, and this reduced the costs and duration of preculture. A few reports on the effect of cryopreservation of the ET of coniferous tree species on their later potential for embryogenesis have shown that the proliferation potential of ET is the same as that of non-frozen control tissues (Kartha et al 1988;Lardet et al 2007;Wu et al 2007). However, we observed some differences in the growth rate of fresh ET on day 28 of culture, which amounted to 19.18 ± 2.0 and 16.00 ± 1.5 g in two control variants (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, somatic embryogenesis appears to be an efficient regeneration system. Somatic embryogenesis offers a number of applications as alternative pathways for mass multiplication of elite trees within a short time, germplasm conservation and genetic transformation (Wu et al 2007;GonzalezArnao et al 2008). The somatic embryogenesis process possesses immense potential for large-scale propagation with high commercial prospects.…”
Section: Introductionmentioning
confidence: 99%
“…a biomass increase, a regeneration potential and production of secondary metabolites) is usually carried out using agar cultures in the post-thawing period (Bachiri et al 2000;Winkelmann et al 2004;Chen and Wang 2002;Zhang et al 2001;Suhartono et al 2005;Cho et al 2007;Wu et al 2007). a biomass increase, a regeneration potential and production of secondary metabolites) is usually carried out using agar cultures in the post-thawing period (Bachiri et al 2000;Winkelmann et al 2004;Chen and Wang 2002;Zhang et al 2001;Suhartono et al 2005;Cho et al 2007;Wu et al 2007).…”
Section: Insight Into the Recovery Of Cell Suspension Cultures After mentioning
confidence: 99%